The relationships between achievement focused motivation and critical thinking - Semerci, Cetin (Academic Journals, 2011)
The aim of this research is to address general relationships between achievement focused motivation and critical thinking. Survey method has been used in the research. In this research, regression analysis has been done. The study sample included a total of 772 students in Turkey, attending the Faculties of Education, Ataturk University (216 students), Cumhuriyet University (110 students), Firat University (331 students) and Yuzuncu Yil University (115 students). Data were collected in the spring of 2010. Two scales were applied to the students at the same time; one of them being achievement focused motivation (AFM) scale, developed by Semerci (2010) and the other one being critical thinking scale. The initial critical thinking scale (the California critical Thinking disposition inventory: CCTDI) was first developed by Facione et al. (1998), and it was adapted to Turkish system by Kokdemir (2003). Of the 772 students participating in the study, 396 are male (51.3%) and 376 are female (48.7%). Most of the correlations between sub-dimensions of achievement focused motivation and sub-dimensions of critical thinking skills were found positive. In this study, there is a correlation of 0.34 between AFM and general critical thinking. Results of the multiple regression analysis regarding prediction of AFM demonstrate that CT is a significant instrument of prediction on AFM. As a result of this study, the following statement is suggested: While teaching students how to gain AFM, prior importance should be attached to developing their critical thinking skills.
Keywords: Achievement focused motivation; motivation; critical thinking